Problématiques des chiens à Kuujjuaq : comment une approche de recherche en écosanté peut-elle aider à les résoudre? - Simon, Audrey; Saint-Charles, Johanne; Lévesque, Francis; Ravel, André (HAL CCSD, 2018)
International audience